2015
DOI: 10.1515/ijafr-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of dairy soiled water in a survey of 60 Irish dairy farms

Abstract: Dairy farming in Ireland generates an effluent known as dairy soiled water (DSW), which consists of a relatively dilute mixture of cow faeces, urine, spilt milk and detergents that is typically applied to grassland. However, relatively little is known about the volumes generated, nutrient content and management factors that influence volume and concentration. Sixty dairy farms that had a separate storage tank for storing DSW were selected for this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…The samples collected at both D1 and D2 covered a much shorter period than the other lagoons, which likely reduced the variation seen over these sampling times. Minogue et al (2015) reported a significant effect of sampling date with all biochemical parameters measured on parlor washwater in Ireland; however, no clear seasonal trends were observed. The authors suggested that seasonal trends may have been masked due to the high number of dairies sampled in the study with a large range in management practices, as well as the effects of rainwater input.…”
Section: Seasonal Trends In Physicochemical Characteristics Of Lagoonsmentioning
confidence: 85%
See 2 more Smart Citations
“…The samples collected at both D1 and D2 covered a much shorter period than the other lagoons, which likely reduced the variation seen over these sampling times. Minogue et al (2015) reported a significant effect of sampling date with all biochemical parameters measured on parlor washwater in Ireland; however, no clear seasonal trends were observed. The authors suggested that seasonal trends may have been masked due to the high number of dairies sampled in the study with a large range in management practices, as well as the effects of rainwater input.…”
Section: Seasonal Trends In Physicochemical Characteristics Of Lagoonsmentioning
confidence: 85%
“…Table 1 provides a summary of studies from the U.S., Ireland, New Zealand, England, and Wales that have examined the composition of wastewater generated on dairies (Hickey et al, 1989;Cumby et al, 1999, Singh et al, 2007Martinez-Suller et al, 2010;Minogue et al, 2015). Total N, phosphorus (P), and potasSubmitted for review in July 2016 as manuscript number NRES 11991; approved for publication by the Natural Resources & Environmental Systems Community of ASABE in December 2016.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dairy soiled water (DSW) (variously referred to as dairy effluent (Longhurst et al, 2000;McFarland et al, 2003), dairy dirty water (Cannon et al, 2000;Moir et al, 2005), or milk-house washwater (Joy et al, 2001)), is a variable strength dairy effluent (typical range 1000 -10000 mg 5-day biochemical oxygen demand (BOD 5 ) L -1 ) comprising milking parlour and holding area washings generated in large but variable volumes (27 -148 L cow -1 d -1 ), and is characterised by low dry matter (DM) content (typically < 3 -4%). Nutrient concentrations in DSW vary considerably, typically between 70 to 500 mg total nitrogen (TN) L -1 and 20 to >100 mg total phosphorus (TP) L -1 (Minogue et al, 2015). The volume and strength of DSW is seasonal and depends on farm management practices, including the efficiency of milking systems (Sweeten and Wolfe, 1994), size of herd, and amount of rainfallgenerated runoff from uncovered hard standings (Minogue et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient concentrations in DSW vary considerably, typically between 70 to 500 mg total nitrogen (TN) L -1 and 20 to >100 mg total phosphorus (TP) L -1 (Minogue et al, 2015). The volume and strength of DSW is seasonal and depends on farm management practices, including the efficiency of milking systems (Sweeten and Wolfe, 1994), size of herd, and amount of rainfallgenerated runoff from uncovered hard standings (Minogue et al, 2015). Dairy soiled water is collected separately from dairy slurry and the main disposal route is directly to land via landspreading or irrigation without any prior treatment.…”
Section: Introductionmentioning
confidence: 99%